2005
DOI: 10.2165/00003088-200544001-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Dosing Frequency on the Pharmacokinetics of a Fentanyl HCl Patient-Controlled Transdermal System (PCTS)

Abstract: The amount of fentanyl absorbed from the PCTS increases as a function of time and is independent of both dosing frequency and total number of doses delivered. The fentanyl HCl PCTS is generally safe and well tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The amount of fentanyl absorbed by patients was found to be directly proportional to the magnitude of current applied by the system, with a 170 μA current producing absorption of approximately 40 μg fentanyl and a coefficient of variation similar to that of iv fentanyl infusion (22% and 23%, respectively) (Sathyan et al 2005a). A separate study found that fentanyl absorption increases with time; in the first hour of treatment approximately 40% of each 40 μg bolus dose of fentanyl is absorbed; however after 10 hours of ITS therapy almost 100% of each 40 μg bolus is absorbed (Sathyan et al 2005b). Although the reasons for the increase in fentanyl absorption over time are not entirely clear, it may result from the reversible alterations in the electrical conduction properties of skin that occur during exposure to electric current from the system (Curdy et al 2001).…”
Section: Overview Of Itsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of fentanyl absorbed by patients was found to be directly proportional to the magnitude of current applied by the system, with a 170 μA current producing absorption of approximately 40 μg fentanyl and a coefficient of variation similar to that of iv fentanyl infusion (22% and 23%, respectively) (Sathyan et al 2005a). A separate study found that fentanyl absorption increases with time; in the first hour of treatment approximately 40% of each 40 μg bolus dose of fentanyl is absorbed; however after 10 hours of ITS therapy almost 100% of each 40 μg bolus is absorbed (Sathyan et al 2005b). Although the reasons for the increase in fentanyl absorption over time are not entirely clear, it may result from the reversible alterations in the electrical conduction properties of skin that occur during exposure to electric current from the system (Curdy et al 2001).…”
Section: Overview Of Itsmentioning
confidence: 99%
“…Although the reasons for the increase in fentanyl absorption over time are not entirely clear, it may result from the reversible alterations in the electrical conduction properties of skin that occur during exposure to electric current from the system (Curdy et al 2001). Absorption of fentanyl was not affected, however, by variations in the frequency of dosing or patient characteristics, such as age, gender, ethnicity, and weight (Sathyan et al 2005b). …”
Section: Overview Of Itsmentioning
confidence: 99%
“…The system also avoids the potential for programming errors. 40 According to the fentanyl PCTS Clinical Trial and Routine Practice panels, less nursing time was consumed and fewer tasks were required with fentanyl PCTS than for IV PCA. 41 …”
Section: Fentanyl Delivered By Transdermal Iontophoresismentioning
confidence: 99%
“…3). 48 Although the reasons for the increase in fentanyl absorption over time are not entirely clear, it may result from reversible alterations in the electrical conduction properties of skin that occur during exposure to electric current from the system. Absorption of fentanyl was not affected, however, by variations in the frequency of dosing or patient characteristics, such as age, gender, ethnicity and weight.…”
Section: Pharmacokinetics Of Transdermal Fentanyl Administration: Pasmentioning
confidence: 99%